Esthesioneuroblastoma: Updating Histologic Grading as It Relates to Prognosis. (May 2014) - Gallagher, Kelly K.; Spector, Matthew E.; Pepper, Jon-Paul; McKean, Erin L.; Marentette, Lawrence J.; McHugh, Jonathan B.
Objective: The Hyams grading system has been extensively used to predict prognosis in patients with esthesioneuroblastoma (ENB). However, most studies showing prognostic correlation group grading into I/II versus III/IV, essentially comparing low versus high grade. In addition, these studies include patients with variable treatment regimens, including some that were treated with chemoradiation alone. We aimed to determine whether additional histologic variables correlate with outcome with regard to disease free and overall survival in a series of patients universally treated with anterior skull base resection and +/– adjuvant chemoradiation. Study Design: A retrospective review of 27 patients with ENB was performed. Methods: The sections of tumor from these 27 patients were studied and reviewed with attention to percentage lobularity, degree of pleomorphism, degree of neurofibrillary matrix, and degree of apoptosis. In addition, the presence or absence of rosettes, necrosis, calcification, spindle cells, gland hyperplasia, and bone invasion were noted. Finally, the number of mitoses per high power field and the nature of chromatin (fine vs coarse) were recorded. The histopathologic features of these 27 ENBs were reviewed and correlated with clinical outcome. Results: There were 11 patients with recurrence (40.7% recurrence). There were 5 deaths (81.5% survival). The study cohort's mean overall survival was 158 months and the mean disease-free survival was 70.6 months. In terms of overall survival, necrosis and mitosis (#/10hpf) were significant but not when multivariate analysis was performed, these were not individually significant. In terms of disease-free survival, mitosis (#/10hpf) was significant but not on multivariate analysis. Gland hyperplasia was found to be a positive prognostic variable, associated with longer overall and disease-free survival, but only in combination with no spindle features and without necrosis. Conclusions: An updated histologic grading system may provide more valuable prognostic information in patients with esthesioneuroblastoma treated with a standardized treatment paradigm.